2023
DOI: 10.1186/s12889-023-15474-5
|View full text |Cite
|
Sign up to set email alerts
|

“It’s just a perfect storm”: Exploring the consequences of the COVID-19 pandemic on overdose risk in British Columbia from the perspectives of people who use substances

Abstract: Background Despite the implementation and expansion of public health and harm reduction strategies aimed at preventing and reversing overdoses, rates of overdose-related events and fatalities continue to rise in British Columbia. The COVID-19 pandemic created a second, concurrent public health emergency that further exacerbated the illicit drug toxicity crisis, reinforced existing social inequities and vulnerabilities, and highlighted the precariousness of systems in place that are meant to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Although settings across the United States and Canada have witnessed sharp increases in drug poisoning deaths since the onset of the pandemic which have been attributed to COVID-19 infection control measures and related service access restrictions [ 15 , 21 , 44 ], we found that a majority of participants across all three cities reported no change in their frequency of experiencing non-fatal overdose during the pandemic. This may be explained by several reasons.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although settings across the United States and Canada have witnessed sharp increases in drug poisoning deaths since the onset of the pandemic which have been attributed to COVID-19 infection control measures and related service access restrictions [ 15 , 21 , 44 ], we found that a majority of participants across all three cities reported no change in their frequency of experiencing non-fatal overdose during the pandemic. This may be explained by several reasons.…”
Section: Discussionmentioning
confidence: 78%
“…Combined with increased socioeconomic precarity and disruption in access to essential services, such stressors may have been in part responsible for the observed increase in overall drug use among some participants as a means to cope or self-medicate. Other qualitative studies have documented similar reasons for increases in drug use among people who use drugs during the pandemic including concerns related financial uncertainty, fear of catching COVID-19, and boredom associated with job loss and isolation from one’s family and friends [ 14 , 15 , 21 , 25 ]. In Toronto and Montreal, we further observed that approximately one-third to two-fifths of participants reported experiencing physical violence, witnessing violence, and feeling threatened or unsafe more often than usual during the pandemic.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The opioid epidemic is dynamic; conclusions from one rural site several years ago may not generalize to another rural site more recently, especially because local economic conditions vary across the large swath of rural landmass. The opioid epidemic is also chaotic; there are concerns about toxicity of unregulated substances due to fentanyl contamination, with an increase in related fatal overdose cases from 5% in 2012 to 90% in 2018 (Foreman-Mackey et al, 2023;Hu et al, 2022).…”
mentioning
confidence: 99%